The Effect Of Giving Rose Aromatherapy On Labor Pain - Usmawati, Dian Peni; Dinengsih, Sri; Lail, Nurul Husnul (Jurnal MIDPRO, 2022)
Labor pain as a physiological process occurs due to contraction of the myometrium. Labor pain has a different intensity in each individual. If not handled properly, labor pain and anxiety experienced by the mother can cause trauma. One of the non-pharmacological treatments that can be done is rose aromatherapy. The objective to determine the effect of giving rose aromatherapy to labor pain in the first stage at the Ciputat Fruit Heart Hospital, South Tangerang, Banten Province in 2022. This type of research is a quasi-experimental with a pretest and posttest one group design. The study was conducted at Ciputat Fruits Hospital, South Tangerang, from July to early August 2022. The population of all physiological birth mothers at Ciputat Fruits Hospital, South Tangerang, Banten Province in July 2022, the total sample was 30 people. The sampling technique is purposive sampling. Data were analyzed using univariate and bivariate with the Wilcoxon test. Data were processed using a computer with the SPSS program. Before being given rose aromatherapy, it was found that the intensity of labor pain in the first stage of labor, namely only 1 person (3.3%) experienced mild pain. Meanwhile, after being given rose aromatherapy, it was found that the intensity of labor pain in the first stage of labor, namely those experiencing mild pain, increased to 9 people (30.0%). Statistical test results of the effect of giving rose aromatherapy to labor pain in the first stage at the Ciputat Fruit Heart Hospital, South Tangerang, Banten Province in 2022 (p value 0.000). Aromatherapy of roses is good in helping to reduce the intensity of labor pain during the first active phase. It is hoped that health workers can implement this intervention in maternity clinics to help mothers reduce the intensity of labor pain.